DETERMINAN PERILAKU PEMBELIAN HIJAU PADA GENERASI Z DI INDONESIA - Carina Diah Ayu Larasati; Rita Wijayanti (Sekolah Tinggi Ilmu Ekonomi DR KH EZ Mutaqien, 2022)
ABSTRACK Environmental conditions in Indonesia are getting worse where non-green waste management is not handled optimally so that people, especially generation z, must be aware of ecological problems by implementing green buying behavior. This study aims to identify the factors influencing consumers' green buying behavior in generation z in Indonesia. This type of research is quantitative with primary data obtained through questionnaires. Total sample of 372 Respondents. The method used to determine the sample is purposive sampling technique. Data processing techniques using the SEM-PLS 3.0 Application. The tests used are the Outer Model Test and the Inner Model Test. The results showed that (1) Perceived environmental knowledge, perceived severity, efficacy response, and attitude had a positive and significant effect on green buying behavior. (2) Perceived severity, efficacy response, and perceived responsibility have a positive and significant effect on attitudes. (3) Attitudes mediate the relationship between perceived environmental responsibility and green buying behavior. Attitudes also mediate between perceived severity and green buying behavior and mediate between efficacy responses and green buying behaviors. The results of this study will be useful for policy strategists and government organizations to create campaigns to encourage eco-friendly buying behavior among young consumers.